Case study on amplitude and phase response comparison between DAS and 3C geophone VSP surveys at a test site in Japan - Nakajima, Takahiro; Miyoshi, Takayuki; Hashimoto, Tsutomu; Xue, Ziqiu (Frontiers in Earth Science, 2022)
Distributed Acoustic Sensing (DAS) is now recognized as an effective tool for seismic surveys, and is widely used as the preferred sensor for acquiring dense Vertical Seismic Profiles (VSP). However, DAS has some disadvantages compared to conventional geophone acquisition, such as single-component data, directivity pattern of the sensor, low S/N, etc. In order to apply DAS data to VSP processing, it is important to understand characteristics of DAS measurements. In this paper, we first examine DAS and geophone responses for a VSP survey in a 1D earth model. The relationship of signal amplitude as a function of incident angle and phase shift between wavelets is confirmed. Next, we validate this relationship acquired in a walk-away VSP survey, which is conventionally applied to monitoring of geological CO2 storage. The survey was carried out at a test site in Japan, and we obtained both three-component (3C) geophone data and DAS data using a single-mode fiber installed behind a casing. Observed amplitudes of the first P-waves by DAS and geophone show a very good agreement with theoretical expectations. Finally, we performed imaging using acquired DAS data following the workflow for conventional VSP processing. These basic behaviors of DAS are useful for designing further analyses, such as VSP in deviated wells and full waveform inversion.